2008
DOI: 10.1007/s10554-008-9352-y
|View full text |Cite
|
Sign up to set email alerts
|

Late gadolinium enhancement: precursor to cardiomyopathy in Duchenne muscular dystrophy?

Abstract: Background-Progressive cardiomyopathy is a common cause of death in Duchenne muscular dystrophy (DMD), presumably secondary to fibrosis of the myocardium. The posterobasal and left lateral free wall of the left ventricle (LV) are initial sites of myocardial fibrosis pathologically. The purposes of this study were to assess whether cardiac magnetic resonance imaging (CMRI), utilizing late gadolinium enhancement (LGE), could identify fibrosis in selective areas of the myocardium, and to assess the relationship o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
109
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 26 publications
10
109
0
Order By: Relevance
“…5,25,34,35). Fibrotic lesions are thought to result from myocyte necrosis and subsequent inflammatory response.…”
Section: Grmdmentioning
confidence: 99%
“…5,25,34,35). Fibrotic lesions are thought to result from myocyte necrosis and subsequent inflammatory response.…”
Section: Grmdmentioning
confidence: 99%
“…In addition, based on our findings, we hypothesize that a difficult and inaccurate preoperative echocardiographic evaluation of NMS patients is one reason for unexpected severe perioperative cardiac complications. In patients with advanced NMS, particularly in those with large and rigid thoracic deformities and low BMI, we would recommend that clinicians evaluate the risk of perioperative heart-related events with additional cardiac assessments, such as brain natriuretic peptide, creatine kinase 16) , multigated cardiac radionuclide ventriculography 17) , and cardiac magnetic resonance imaging 18,19) . In this study, several valvular abnormalities (including trivial valve regurgitation) were detected.…”
Section: Discussionmentioning
confidence: 99%
“…In female carriers an ECG and echocardiogram should be performed at diagnosis or after the age of 16 years and at least every 5 years thereafter, or more frequently in patients with abnormalities on investigation or carriers with severe skeletal muscle symptoms or cardiac symptoms. detect cardiac fibrosis in patients with Duchenne muscular dystrophy [12,13]. The study showed, that late gadolineum enhancement was negative related to left ventricular ejection fraction.…”
mentioning
confidence: 91%